Bruise Responses of Apple-to-Apple Impact. Issue 16 (2016) - Fu, Han; He, Long; Ma, Shaochun; Karkee, Manoj; Chen, Du; Zhang, Qin; Wang, Shumao
Abstract: Currently, no commercial success has been achieved for mechanized or automated harvesting of fresh market apples. Automated or robotic harvesting systems have primarily been limited by the speed, accuracy, robustness and cost of the machine. Bulk harvesting has a potential to address these challenges but the technique suffers from a high level of harvest-induced fruit damage. To gain an understanding of bruising potential during fruit-to-fruit collision that occurs during bulk harvesting, apple-to-apple impact tests were carried out in a laboratory using a specially design pendulum-type apple bruising test device. This device could attach a half-apple on its pendulum impactor with its middle zone as the impacting surface to apply an impact force on different surfaces of a whole apple placed on a stationary platform of the device to quantitatively study the effects of different impacts. Three impact patterns of middle-to-top, middle-to-middle and middle-to-bottom zone between two apple specimens were tested using "Granny Smith" apples. Six to seven different levels of impact forces were applied for each test pattern. Obtained results revealed that if the impact force were less than 16 N it would result in no bruising on apple specimen in all test conditions. This particular variety of apple could tolerate a moderate impact force of 28 N and still maintain an "Extra Fancy" quality over 98% for all tested fruit. This study also showed that, if the impact force could be controlled on a level less than 53 N, about 94% or more apples could still meet a "fresh-market" quality threshold.